2022
DOI: 10.3389/fcell.2022.1008506
|View full text |Cite
|
Sign up to set email alerts
|

Genome elimination from the germline cells in diploid and triploid male water frogs Pelophylax esculentus

Abstract: Hybridogenesis is a hemiclonal reproductive strategy in diploid and triploid hybrids. Our study model is a frog P. esculentus (diploid RL and triploids RLL and RRL), a natural hybrid between P. lessonae (LL) and P. ridibundus (RR). Hybridogenesis relies on elimination of one genome (L or R) from gonocytes (G) in tadpole gonads during prespermatogenesis, but not from spermatogonial stem cells (SSCs) in adults. Here we provide the first comprehensive study of testis morphology combined with chromosome compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 76 publications
2
12
0
Order By: Relevance
“…We were, therefore, interested in whether the synthesized P. esculentus progeny eliminates preferentially parental genomes of P. ridibundus or P. lessonae . In all but one case P. esculentus tadpoles eliminated mostly lessonae genome and retained ridibundus genome in their germ cells, well in agreement with previous studies (Chmielewska et al, 2022; Dedukh et al, 2019; Dedukh & Krasikova, 2022). Neither the direction of the cross nor the origin of maternal mtDNA had any effect on an overrepresentation of ridibundus hemiclones.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We were, therefore, interested in whether the synthesized P. esculentus progeny eliminates preferentially parental genomes of P. ridibundus or P. lessonae . In all but one case P. esculentus tadpoles eliminated mostly lessonae genome and retained ridibundus genome in their germ cells, well in agreement with previous studies (Chmielewska et al, 2022; Dedukh et al, 2019; Dedukh & Krasikova, 2022). Neither the direction of the cross nor the origin of maternal mtDNA had any effect on an overrepresentation of ridibundus hemiclones.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the analysis of micronuclei, it has been suggested that P. lessonae chromosomes were eliminated. Yet, it has never been confirmed (Chmielewska et al, 2022;Dedukh et al, 2019Dedukh et al, , 2020. Here, using a newly developed marker specific for P.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations